Incidence, outcomes and prognostic factors during 25 years of treatment of chondrosarcomas. (September 2018) - ,; van der Geest, Ingrid C.; Bramer, Jos A.; Schaap, Gerard R.; Jutte, Paul C.; Schreuder, HW Bart; Ploegmakers, J.J.W.; van Praag (Veroniek), V.M.; Rueten-Budde, A.J.; Ho, V.; Dijkstra, P.D.S.; Fiocco, M.; et al.
Abstract: Background: There are few studies detailing the incidence, patient outcomes and prognostic factors for chondrosarcomas (CS). Those that do exist have small sample sizes and/or use older datasets. The purpose of this study was to determine the incidence, overall survival (OS) and prognostic factors for OS of CS patients, as well as investigate the efficacy of curettage. Methods: We analyzed data of 2186 patients diagnosed with chondrosarcomas between '89-'13 from the Netherlands Cancer Registry. The effect of risk factors on OS was assessed with a multivariate Cox regression. Median Follow-up was determined with reversed Kaplan-Meier. OS was estimated using Kaplan-Meier method. Results: The relative incidence of CS was 2.88 per million citizens between '89-'96, 4.15 between '96-'04 and 8.78 between '05-'13. Most of the increase in incidence came from atypical cartilaginous tumours/grade I chondrosarcoma (ACT/CS I). The 3-, 5- and 10-years survival were, respectively, 96%, 93% and 88% for ACT/CS I, 82%, 74% and 62% for grade II CS and 38%, 31% and 26% for grade III CS. Prognostics factors significantly associated with OS were age, histological grade, year of diagnosis, tumour location and size. Conclusion: The incidence of CS, and especially ACT/CS I, has increased over time, which could be driven by both an ageing population and increased diagnostic imaging. With the increased number of diagnosed ACT/CS I, the number of preventative curettages of this tumour has also increased. Despite the supposed preventative character of this treatment, the incidence of high-grade CS did not decrease. Highlights: The group of diagnosed ACT/CS I is rapidly growing. Increases could be driven by an ageing population and increased diagnostic imaging. We provide a large sample size for a prognostic model for chondrosarcomas. Age, tumor grade, -size and -localization and time are prognostic factors for OS. Does treatment of ACT/CS I with curettage outweighs the potential benefits?